KETAHANAN HIDUP Drosophila melanogaster dan Drosophila ananassae - Lamangantjo, Chairunnisa (Sainstek, 2009)
This research aim to observe of Drosophila melanogaster and D. ananassae mortality and survively. It conducted at Genetic Laboratory in Biologys Departement Gorontalo State University. Data Analyzes that used to known a value of mortality was the analyzes of Mortality and Survively. The results showed that the highest mortality rate = 19,28% (k = 0,09) was seen on D. melanogaster, whereas the highest survivor (k = 0,06) was seen on D. ananassae ( mortality rate = 12,58%).